CRISIS AND DISASTER MANAGEMENT CHOICE STRATEGY - AP, Kunto Wibowo (Advances in Social Sciences Research Journal, 2020)
Predicting the occurrence of a crisis is indeed difficult, where insensitivity picks up signals from existing symptoms, causing it to only realize when the crisis situation. If you are not able to handle it will have bad consequences, and even the impact can not be predicted when it ends. Therefore, optimal efforts to reduce risks and uncertainties are carried out during a crisis, so that crisis management is needed to quickly return to normal. Risk conditions are conditions that have an impact on a situation such that it can cause a crisis or even a disaster. Crisis is a situation of very high potential towards disaster in a short span of time. While disasters are events that threaten and disrupt life and livelihoods caused by natural factors and / or factors not natural or human factors, causing casualties, environmental damage, property losses, and psychological impacts. So, crises and disasters require proper management. Accordingly, comparative advantage as a strategy can be a choice for crisis and disaster management.